ChemInform Abstract: Efficient Synthesis of Dihydropyrido[4, 3‐d]pyrimidines by Microwave‐Promoted Three‐Component aza‐Diels—Alder Reaction. Issue 16 (28th March 2013) - Sarmah, Manas M.; Sarma, Rupam; Prajapati, Dipak; Hu, Wenhao
Abstract A facile synthesis of the title compounds is achieved by microwave promoted three‐component aza‐Diels—Alder reaction of uracil derivative (I), aldehydes, and amines.